Preoperative hypoalbuminemia is an independent risk factor for increased high-grade morbidity after elective rectal cancer resection - Hardt, Julia; Pilz, Lothar R.; Kienle, Peter; Post, Stefan; Magdeburg, Richard (International journal of colorectal disease, 2017)
Purpose: This study investigated the association of preoperative hypoalbuminemia and postoperative complications after elective resection for rectal cancer. Methods: From September 2009 to December 2014, all patients who underwent elective rectal resection for adenocarcinoma of the rectum were identified using a prospective colorectal cancer database. Hypoalbuminemia was defined as a serum albumin < 35 g/L. Characteristics and outcomes of hypoalbuminemic patients were compared to those of patients with normal albumin levels. Potential risk factors for postoperative major morbidity, defined as Clavien-Dindo ≥ grade 3, were analyzed by both univariate and multivariate analyses. Results: Three hundred seventy patients met the inclusion criteria. Hypoalbuminemic patients (67/370 (18%)) were significantly older and had more advanced tumor stages and more comorbidities (more ASA III, higher percentage of diabetics). Furthermore, they were more likely to undergo abdominoperineal resection instead of low anterior resection and less likely to be operated laparoscopically. On univariate analysis, a higher BMI, advanced tumor stages, diabetes, open procedures, pre- and postoperative hypoalbuminemia, a higher decrease in albumin (∆ preop-postop), and conversion were significantly associated with postoperative high-grade morbidity. On multivariate analysis, diabetes, advanced tumor stages, a higher decrease in the albumin level, as well as preoperative hypoalbuminemia turned out to be independent risk factors for postoperative high-grade morbidity. Conclusions: Hypoalbuminemia is an independent risk factor for postoperative high-grade morbidity. As a low-cost and easy accessible test, serum albumin should be used as a prognostic tool to detect patients at risk for adverse outcomes after resection for rectal cancer.